Association of the atherogenic index of plasma and other lipid indices with abnormal glucose metabolism in patients with ischemic stroke - Liu, Ting; Li, Weizhen; Zhang, Shiwen; Wang, Ye; Zou, Xin; Zhao, Yiran; Dong, Jiawen; Zhu, Lin; Luo, Shencheng; Kolberg, Bernhard; Li, Jing (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the relationship of the atherogenic index of plasma (AIP) and other lipid indices with prediabetes mellitus (Pre-DM) and type 2 diabetes mellitus (T2DM) in patients with ischemic stroke (IS), with a focus on exploring the clinical application value of AIP in the assessment of glucose metabolism disorders.MethodsThis study was conducted for the first time based on a large-scale IS cohort. 18,604 patients with IS were enrolled and subjected to comprehensive lipid profile assessments. The correlation between AIP and other commonly used lipid indices was systematically compared. Based on glucose levels, the patients were divided into three groups: normal glucose (NG), Pre-DM, and T2DM. The relationship of AIP and other lipid indices with Pre-DM and T2DM was evaluated through multivariable logistic regression. Furthermore, the dose-response correlation of AIP with Pre-DM and T2DM across varying genders and age groups was explored through the Restricted Cubic Spline (RCS) model, which was employed to analyze non-linear associations between variables.ResultsWe found that triglyceride (TG), total cholesterol (TC)/high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C)/HDL-C, TG/HDL-C, non-HDL-C, remnant cholesterol (RC), RC/HDL-C, and AIP were all positively correlated with Pre-DM and T2DM. Notably, AIP demonstrated the highest specificity in this context. AIP was then divided into tertiles, with the T3 group showing the strongest correlation with both conditions compared with the T1 group. The correlation was stronger among females and patients aged ≥60 years. RCS analysis further indicated a non-linear positive dose-response relationship between AIP and T2DM across all genders and ages.ConclusionIn IS patients, AIP exhibits a stronger association with Pre-DM and T2DM than other lipid indices, especially in female patients and those aged 60 years and above.